Evidences about causes of wildfires in the Northern Region of Portugal = As causas e as motivações dos incêndios florestais na Região Norte de Portugal - Tedim, Fantina (2019)
This paper reports the results of an analysis of the causes of wildfires in the NorthernRegion of Portugal for the period 2012-2014. Data were analysed using descriptivestatistics, GIS, cluster analysis and kernel density estimation. Analysis shows that themajority of wildfires have unknown causes, followed by those caused by negligenceand those started deliberately. This research showed that the Northern Region is nota homogenous space in terms of the causes of and reasons for wildfires. Problemswith misconceptions in ascribing causes are identified and discussed.